Techno-Economic Analysis of Candidate Oxide Materials for Thermochemical Storage in Concentrating Solar Power Systems - Buck, Reiner; Agrafiotis, Christos; Tescari, Stefania; Neumann, Nicole; Schmücker, Martin (Frontiers in Energy Research, 2021)
The thermal storage capability is an important asset of state-of-the-art concentrating solar power plants. The use of thermochemical materials, such as redox oxides, for hybrid sensible/thermochemical storage in solar power plants offers the potential for higher specific volume and mass storage capacity and as a consequence reduced levelized cost of electricity making such plants more competitive. For the techno-economic system analysis, three candidate redox materials were analyzed for their cost reduction potential: cobalt-based, manganese–iron–based, and perovskite-based oxide materials. As a reference process the use of inert commercial bauxite particles (sensible-only storage) was considered. A solar thermal power plant with a nominal power of 125 MWe and a storage capacity of 12 h was assumed for the analysis. For each storage material a plant layout was made, taking the specific thermophysical properties of the material into account. Based on this layout a particle break-even cost for the specific material was determined, at which levelized cost of electricity parity is achieved with the reference system. Cost factors mainly influenced by the material selection are storage cost and steam generator cost. The particle transport system cost has only a minor impact. The results show differences in the characteristics of the materials, for example, regarding the impact on storage size and cost and the steam generator cost. Regarding the economic potential of the candidate redox materials, the perovskite-based particles promise to have advantages, as they might be produced from inexpensive raw materials.